2023
DOI: 10.1007/s00431-023-04887-4
|View full text |Cite
|
Sign up to set email alerts
|

Relationships of BMI, muscle-to-fat ratio, and handgrip strength-to-BMI ratio to physical fitness in Spanish children and adolescents

Abstract: This study aimed to determine the relationship of body mass index (BMI), muscle-to-fat ratio (MFR), and handgrip strength-to-BMI ratio to physical fitness parameters in an active young population according to sex across four different time points. A total of 2256 Spanish children and adolescents (aged 5–18) from rural areas participating in an extracurricular sport in different municipal sports schools participated in this study. Participants were divided into children (5–10 years) and adolescents (11–18 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 53 publications
(52 reference statements)
1
7
0
Order By: Relevance
“…In terms of the 6 min walk and VAM-EVAL tests, the best predictor was BMI. These findings are in line with previous results ( Manzano-Carrasco et al, 2023 ). Considering the importance of cardiorespiratory fitness levels for health in the young adults males ( Ortega et al, 2018 ; Agostinis-Sobrinho et al, 2022 ), BMI might be considered as a predictor of aerobic fitness tests.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In terms of the 6 min walk and VAM-EVAL tests, the best predictor was BMI. These findings are in line with previous results ( Manzano-Carrasco et al, 2023 ). Considering the importance of cardiorespiratory fitness levels for health in the young adults males ( Ortega et al, 2018 ; Agostinis-Sobrinho et al, 2022 ), BMI might be considered as a predictor of aerobic fitness tests.…”
Section: Discussionsupporting
confidence: 94%
“…BMI has been widely used to quantify body fat and identify people who are overweight ( Qin et al, 2022 ) which have negative consequences for the health of children (e.g., dyslipidemia, arterial stiffness, and less cardio-respiratory capacity) ( Vaara et al, 2013 ; Abdelkarim et al, 2020 ) and adults (e.g., risk of heart attack) ( Jafari et al, 2019 ). Several studies have identified that a high BMI is related to poor cardiorespiratory fitness and vertical jump ( Qin et al, 2022 ; Manzano-Carrasco et al, 2023 ), which is linked to effects by the kind of sport done on physical fitness ( Tahira, 2021 ). In this sense, regular sport participation could be a great strategy to increase fitness and combat the consequences of high BMI ( Tahira, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…VO 2 max is directly correlated with HGS, a strong predictor of cardiovascular health in both young adults and children [ 13 , 14 , 16 ]. Recently, children with overweight/obesity showed higher HGS and lower CRF compared to their normal weight counterparts [ 16 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is now evidence that low HGS may be associated with poor cardiometabolic outcomes in children and adolescents too [ 15 ]. In a recent observational study in 2256 children and adolescents aged 5–18 years, HGS-to-body mass index (BMI) presented a positive correlation with cardiorespiratory fitness [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…HGS has been widely investigated for its relationship with disease prevalence and associated factors in the adolescent population in order to identify groups more prone to low levels of muscle strength (Bim, Pinto, Scarabelot, et al, 2021; Ng et al, 2019; Silva et al, 2017). Body mass index (BMI) was found to be directly related to HGS, indicating that adolescents with overweight (including obesity) have higher HGS (Bim, Pinto, Scarabelot, et al, 2021; Bim, Pinto, Silva, et al, 2021; Manzano‐Carrasco et al, 2023; Ng et al, 2019; Silva et al, 2017). This finding, however, is controversial because, when HGS is normalized to body weight, the association with obesity indicators seems to change direction (Lima et al, 2022).…”
Section: Introductionmentioning
confidence: 99%